ANALISIS PRODUKTIVITAS DAN PENDAPATAN TENAGA KERJA PENYADAP KARET DI KABUPATEN JEMBER - Retno Harieswantini; Hariadi Subagja; Muksin Muksin (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Rubber plantation development has proven to be the economic driver of the region with a variety of multiplier effect. East Java is one of the potential areas for rubber plantations development. Rubber production in East Java in 2012 amounted to 6,085 tons. This study aims to determine the factors that influence the labor productivity of rubber tappers and differences in productivity, revenue, revenue contributions. This research was conducted by taking locations in Jember by taking Sumberwadung and Durjo plantations as research objects. Data analysis technique used is multiple linear recreation and different test. The analysis show: Labor productivity in plantation rubber tapper Sumberwadung influenced by the outpouring of hours of work, education and training and the environment and work climate. Labor productivity in plantation rubber tapper Durjo influenced by age, environment and climate and the number of family members.Productivity and revenue between growers and Durjo Sumberwadung no different. Labor income between growers and Durjo different Sumberwadung